Does ethnicity affect where people with cancer die? A population-based 10 year study. - Jonathan Koffman; Yuen King Ho; Joanna Davies; Wei Gao; Irene J Higginson (PLoS ONE)
Background Ageing is a growing issue for people from UK black, Asian and minority ethnic (BAME) groups. The health experiences of these groups are recognised as a 'tracer' to measure success in end of life patient-preferred outcomes that includes place of death (PoD). Aim To examine patterns in PoD among BAME groups who died of cancer. Material and methods Mortality data for 93,375 cancer deaths of those aged ≥65 years in London from 2001-2010 were obtained from the UK Office for National Statistics (ONS). Decedent's country of birth was used as a proxy for ethnicity. Linear regression examined trends in place of death across the eight ethnic groups and Poisson regression examined the association between country of birth and place of death. Results 76% decedents were born in the UK, followed by Ireland (5.9%), Europe(5.4%) and Caribbean(4.3%). Most deaths(52.5%) occurred in hospital, followed by home(18.7%). During the study period, deaths in hospital declined with an increase in home deaths; trend for time analysis for those born in UK(0.50%/yr[0.36-0.64%]p<0.001), Europe (1.00%/yr[0.64-1.30%]p<0.001), Asia(1.09%/yr[0.94-1.20%]p<0.001) and Caribbean(1.03%/yr[0.72-1.30%]p<0.001). However, time consistent gaps across the geographical groups remained. Following adjustment hospital deaths were more likely for those born in Asia(Proportion ratio(PR)1.12[95%CI1.08-1.15]p<0.001) and Africa(PR 1.11[95%CI1.07-1.16]p<0.001). Hospice deaths were less likely for those born in Asia(PR 0.73 [0.68-0.80] p<0.001), Africa (PR 0.83[95%CI0.74-0.93]p<0.001), and 'other' geographical regions (PR0.90[95% 0.82-0.98]p<0.001). Home deaths were less likely for those born in the Caribbean(PR0.91[95%CI 0.85-0.98]p<0.001). Conclusions Location of death varies by country of birth. BAME groups are more likely to die in a hospital and less likely to die at home or in a hospice. Further investigation is needed to determine whether these differences result from patient-centred preferences, or other environment or service-related factors. This knowledge will enable strategies to be developed to improve access to relevant palliative care and related services, where necessary.